2015
DOI: 10.1088/0957-4484/26/25/255101
|View full text |Cite
|
Sign up to set email alerts
|

Novel alginate-based nanocarriers as a strategy to include high concentrations of hydrophobic compounds in hydrogels for topical application

Abstract: The cutaneous penetration of hydrophobic active molecules is of foremost concern in the dermatology and cosmetic formulation fields. The poor solubility in water of those molecules limits their use in hydrophilic forms such as gels, which are favored by patients with chronic skin disease. The aim of this work is to design a novel nanocarrier of hydrophobic active molecules and to determine its potential as an ingredient of a topical form. The nanocarrier consists of an oily core surrounded by a protective shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 76 publications
5
27
0
Order By: Relevance
“…In the case of free Nile Red, this phenomenon was very poor. Therefore our findings corroborate the hypothesis [24] that this particular type of carrier is not able to lead to a transdermal delivery of the drug. These results encouraged us to perform DSC analysis of SC after permeation study of Eb-NCS 3 for 12 h to detect possible effects on structure of this part of skin, based on thermal properties.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the case of free Nile Red, this phenomenon was very poor. Therefore our findings corroborate the hypothesis [24] that this particular type of carrier is not able to lead to a transdermal delivery of the drug. These results encouraged us to perform DSC analysis of SC after permeation study of Eb-NCS 3 for 12 h to detect possible effects on structure of this part of skin, based on thermal properties.…”
Section: Discussionsupporting
confidence: 90%
“…Our goal in this study was to find enhanced Eb repurposing as an antifungal agent through encapsulation in an appropriate nanosized system dedicated for topical delivery. Therefore, we encapsulated Eb-NCS using ultrasound oil-in-water emulsification, followed by gelation with calcium ions according to the method reported by Nguyen et al [24]. This robust method allowed successful entrapment of this active compound in the nanosized system at room temperature and without the use of organic solvent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been demonstrated that nanoencapsulation of lipophilic molecules can increase their concentration in a gel while keeping its pH, rheological or sensory properties unchanged [12,13]. Moreover, nanosystems have also been used to disperse homogeneously an active molecule in films for transdermal or dermal delivery [6,10,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, our focus is on novel crosslinkers based on hydrophobic polyphenolic compounds for the modulation of the LCST of NIPAAm within a crosslinked matrix. Curcumin is a naturally derived hydrophobic polyphenol and is known for its numerous biological activities (e.g., demonstrated anti-cancer, anti-oxidation and anti-inflammatory properties) [29, 30]. Clinical trials suggested that curcumin was well tolerated by the human body, even at relatively high dosages (12 g/day) [3133].…”
Section: Introductionmentioning
confidence: 99%